Increasing the Growth and Production of Alfalfa by Supplementation with Various Types of Organic Fertilizers and Arbuscular Mycorrhizal Fungi - Sabilah, Inka Shal Sabilah; Prihantoro, Iwan; Permana, Asep Tata (Faculty of Animal Science, Universitas Brawijaya, 2024)
This study aimed to evaluate the effects of various organic fertilizers and arbuscular mycorrhizal fungi (AMF) on the growth and production of alfalfa plants in the tropics. This study used a completely randomized design (CRD) factorial pattern consisting of two factors with ten replications. Factor A included the types of organic fertilizer, including chicken manure, cow manure, goat manure, and vermicompost. Factor B was the dose of AMF, which included 0 g and 10 g. The results revealed an interaction effect (p<0,01) between the type of organic fertilizer and AMF factors on AMF colonization in alfalfa roots and leaf chlorophyll. The single factor of the type of organic fertilizer had a very significant effect (p<0,01) on increasing the pH, plant height, number of branches, number of leaves, root fresh weight, shoot fresh weight, and shoot dry weight of the media. Moreover, the single factor AMF had no significant effect (p>0,05) on the observed parameters. In conclusion, the application of various types of organic fertilizers with 20% media volume effectively increased the growth and production of alfalfa plants, and the type of organic fertilizer, cow manure, was the best treatment. The application of organic fertilizers alone or in combination with 10 g of AMF did not significantly affect the growth and production of alfalfa plants